Study of some mechanical variables and the relationship with achievement in triple jump of youth. - N. Mahmod, ahmed; R. Hameed, Intisar (Journal of Physical Education, 2012)
The moments upgrade in triple jump stages require group of mechanical variables to achieve the ideal form , this study interested in showing the relationship between some mechanical variables to the moments upgrade (Approach Angle, seek time, flight time, distance achieved for each stage of upgrade with the achievement. Aim of the study is identify some mechanical variables to stages of upgrading and its relationship with the achievement. Hypothesis of the study is presence statistically significant relationship between mechanical variables and the achievement. The study have included research sample the players national youth team in triple jump (8) players. We found the relationship between variables to the moments upgrade (Approach Angle, advance Angle, seek time, flight time, distance achieved for each stage of upgrade with achieved in triple jump using the kinetic analysis reference to the kinovea program .Concludtion of the study is observed the variable have close correlation with achievement of triple jump.